Perkembangan pada masa pranatal dan kelahiran: masa kelahiran - Mamun Hanif; fahmy maulana (Universitas Islam Raden Rahmat Malang, 2025)
Until now, there are still some people who think that a child’s development begins when he is born into the world. In fact, development can be observed during the early stages of ovulation. The meeting between mature sperm cells and mature egg cells then fertilization occurs. From here on, the development of the future baby can be observed and studied. There are many things that everyone, especially prospective parents, should know about child development issues starting from the period before birth or what is often called prenatal until birth. Because these two periods are important and determine the development of children in the following years until their old age. This study aims to provide some knowledge about child development in the prenatal or prenatal period and during birth. This study uses the Library Research method by examining several data sources from books related to prenatal development and birth. The conclusion of this study is that prenatal development and birth have a very important influence on the child’s development in the subsequent development period. There are several things that must be considered so that the child experiences perfect development from the stage of conception until he is ready to be born into the world, as well as several things that must be done by fathers and mothers in order to maintain good development for the baby and good conditions for the mother.